2014
DOI: 10.3390/molecules191119007
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Eucalyptus Gunnii Hook. As a Novel Source of Antioxidant, Antimutagenic and Antibacterial Agents

Abstract: Abstract:The present study describes radical scavenging capacity (RSC), antimutagenic and antibacterial properties of the essential oil (EO) of the leaves of Eucalyptus gunnii Hook. (Southern Montenegro). Chemical composition was evaluated by gas chromatographymass spectrometry (GC-MS). In oil, 1,8-cineole (67.8%) and α-pinene (14.12%) were the major compounds comprising almost 82% of total EO. EO exhibited moderate DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging activity, with IC50 value of 7.19 µL/mL. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
5
21
0
1
Order By: Relevance
“…The chemical composition of the analyzed E. gunnii EO is quite similar to data reported in literature. 1,8 Cineole was confirmed as the main component, as described in previous studies, with a percentage ranging from 17.9 to 67.8% (Lucia et al, 2008;Bugarin et al, 2014). Conversely, spathulenol (16.5%) was reported as the major component of E. gunnii EO from Tunisia (Elaissi et al, 2011) and it was identified also in E. gunnii EO from Argentina with a percentage of 12.3% (Lucia et al, 2008).…”
Section: Chemical Composition Of Essential Oilssupporting
confidence: 62%
See 2 more Smart Citations
“…The chemical composition of the analyzed E. gunnii EO is quite similar to data reported in literature. 1,8 Cineole was confirmed as the main component, as described in previous studies, with a percentage ranging from 17.9 to 67.8% (Lucia et al, 2008;Bugarin et al, 2014). Conversely, spathulenol (16.5%) was reported as the major component of E. gunnii EO from Tunisia (Elaissi et al, 2011) and it was identified also in E. gunnii EO from Argentina with a percentage of 12.3% (Lucia et al, 2008).…”
Section: Chemical Composition Of Essential Oilssupporting
confidence: 62%
“…In light of this, it could be used as an alternative insecticidal strategy, leading to the development of biodegradable and nontoxic products (Purwatiningsih et al, 2012). Several studies reported the antifungal activity of the EO of L. petersonii on Candida albicans and several Aspergillus species (Hood et al, 2010;Kim and Park, 2012) and its antibacterial efficacy (Lis-Balchin et al, 1996;Demuner et al, 2011;Bugarin et al, 2014;Van Vuuren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, a growing number of studies have identified different plants extracts with antigenotoxic potential, such as: Mentha longifolia (Al-Ali et al 2014), Dioscorea pentaphylla (Prakash et al 2014), Lilium candidum (Jovtchev et al 2014), Eucalyptus Gunnii (Bugarin et al 2014), Camellia sinensis (Bhattacharya et al 2014), Curcuma longa (Liju et al 2014), Celtis iguanaea (Borges et al 2013), Solanum paniculatum (Vieira et al 2013), Synadenium umbellatum (Melo-Reis et al 2011), Ginkgo biloba (Vilar et al 2009), and others. Thus, there has been growing interest in finding and using natural plant products to reduce genotoxic and/or carcinogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, allelopathic effect of this essential oil against many weeds was also reported by many researchers (Batish et al, 2004;Verdeguer et al, 2009;Rassaeifar et al, 2013). Eucalyptus essential oil was also reported as an effective anti-inflammatory, analgesic, antioxidant, antimutagenic, insecticide, nematocide and acaricide oil (Batish et al, 2008;Bugarin et al, 2014;Rossi & Palacios, 2015).The Eucalyptus essential oils can be obtained by different methods, such as hydrodistillation, supercritical CO2 extraction, microwave-assisted extraction, and vacuum extraction by solvents. These methods affect the final yield of the oil and it varied from 0.1± 0.1 to 5.7±0.5 7% (Elaissi et al, 2010a;Elaissi et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%